Perspectivas para a clínica psicanalítica da dor crônica - Castro, Filipe Caldeira (2023)
This research is interested in a phenomenon that delimits insufficiencies in health sciences and raises contradictions in the psychoanalytic field: chronic pain. More precisely, we will address the perspectives of a psychoanalytic clinic with this condition, once it is a clinic that fundamentally affects the body, and which presents impasses on symbolic capacities, we investigated the main attributes that permeate the psychoanalytic clinic with chronic pain, reflecting on the representational dilemmas of pain that are presented in the scope of the transferential relationship. The research had the collaboration of three participants, who are affectionately named in this text by Maria, Rosa and Ana. Participants were invited to perform individual clinical sessions over a period of eight consecutive months with a minimum frequency of one session per week. Aiming to build an overview of the psychoanalytic clinic of chronic pain, the text in question sought to organize, from clinical cases, elements that constitute and permeate the analyzes of these cases. Initially, we present the theoretical conceptions of body and pain used during the work. Then, we disseminate the applied methodology of analysis with the exposition of elements that can serve as a key to read the text. After that, the clinical cases were presented with the analyzes of data relevant to the research. Next, we discuss some informative aspects of contemporary language and the formation of the phenomenon of symbolic chronification. And, at the end, we apply a structural analysis of research to the elaboration of clinical models that allow a look at the direction of this clinical specificity. We take into account that all the small unread fragments of these subjects make up a possible interpretation for the unconscious allegory that constitutes their stories.